2021
DOI: 10.3390/antiox10060895
|View full text |Cite
|
Sign up to set email alerts
|

Serum 5-Hydroxyindoleacetic Acid and Ratio of 5-Hydroxyindoleacetic Acid to Serotonin as Metabolomics Indicators for Acute Oxidative Stress and Inflammation in Vancomycin-Associated Acute Kidney Injury

Abstract: The incidence of vancomycin-associated acute kidney injury (VAKI) varies from 5–43%, and early detection of VAKI is important in deciding whether to discontinue nephrotoxic agents. Oxidative stress is the main mechanism of VAKI, and serotonin (5-HT) and its metabolite 5-hydroxyindoleacetic acid (5-HIAA) have been examined with respect to their involvement in ischemia/reperfusion damage in experimental animal models. In the current study, we assessed 5-HT and 5-HIAA as novel biomarkers for detecting VAKI in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…Previous studies have shown that oxidative stress is an important mechanism related to glycopeptide antibiotics, such as vancomycin, bleomycin, etc.,induced cytotoxicity [39][40][41].It has been documented that TIGAR prevents apoptosis via directing glucose to PPP and increasing the levels of NADPH and 5-ribose phosphate, thus signi cantly reducing intracellular ROS [13,38]. Here, we observed that teicoplanin caused ROS accumulation in HEI-OC1 cells, and the overexpression of TIGAR decreased the cellular level of ROS and the loss of ΔΨm in HEI-OC1 cells exposed to teicoplanin, but TIGAR knockdown has the opposite effect (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies have shown that oxidative stress is an important mechanism related to glycopeptide antibiotics, such as vancomycin, bleomycin, etc.,induced cytotoxicity [39][40][41].It has been documented that TIGAR prevents apoptosis via directing glucose to PPP and increasing the levels of NADPH and 5-ribose phosphate, thus signi cantly reducing intracellular ROS [13,38]. Here, we observed that teicoplanin caused ROS accumulation in HEI-OC1 cells, and the overexpression of TIGAR decreased the cellular level of ROS and the loss of ΔΨm in HEI-OC1 cells exposed to teicoplanin, but TIGAR knockdown has the opposite effect (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Study design and subject selection are summarized in Figure 4 . The current study included subjects from our previous study cohort [ 66 ]. In brief, 23,182 cases referred for vancomycin concentration measurement from January 2018 to December 2019 were screened.…”
Section: Methodsmentioning
confidence: 99%
“…A recent human study demonstrated that lower serum serotonin (5-HT), higher serum 5-hydroxy indole acetic acid (5-HIAA), and a higher ratio of 5-HIAA to 5-HT was associated with the occurrence of VA-AKI. The finding suggests that the high 5-HIAA/5-HT ratio could be a potential surrogate biomarker for VA-AKI, and indicates that acute oxidative stress and inflammation are involved in in the mechanism of VA-AKI [32].…”
Section: Oxidative Stressmentioning
confidence: 86%
“…As mentioned earlier, a high 5-HIAA/5-HT ratio in serum (AUC 0.88 (0.88-0.96)) was proposed as a potential surrogate biomarker for VA-AKI in humans [32]. Furthermore, Kim et al retrospectively compared serum biomarkers among patients with and without VA-AKI.…”
Section: Biomarkers For Detecting Va-akimentioning
confidence: 99%